(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aimed at the possibility of achieving organizational superiority through strategic intelligence by dimensioning (vision, future, motivation, creativity) to meet the challenges faced by the managers of middle departments in the Ministry of Planning, which are responsible for providing services to a large segment of society, as the study problem is focused on knowing (what They are the challenges facing the Ministry’s adoption of strategic intelligence as a decisive and effective mechanism in achieving organizational excellence. The study aims to diagnose and interpret the correlation and influence relationship between the two research variables (strategic intelligence, and organizational excellence). The departments and divisions in the general insurance companies and the data were processed and analyzed using the statistical program (SPSS(to reach the required results, the research reached a set of conclusions, the most important of which was the existence of a significant impact relationship for the independent variable strategic intelligence and the dependent variable represented by organizational superiority. of its culture because of its impact on its organizational superiority.